2019
DOI: 10.2147/ijnrd.s185691
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient engagement activities with health care professionals in continuous ambulatory peritoneal dialysis therapy: an exploratory pilot study</p>

Abstract: Background: This pilot study aimed to explore the engagement activities between patients on continuous ambulatory peritoneal dialysis (CAPD) therapy and their health care professionals. Methods: An exploratory qualitative study was conducted. In-depth semi-structured interviews were undertaken involving four CAPD patients who were selected through purposive sampling. The participants were asked questions about their engagement experiences with their health care professionals. Results: Six main engagement activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 13 , 35 Patient self-care abilities can be obtained through structured training patterns or criteria to enhance knowledge, skills, and attitudes. 54 , 55 Poorly performed self-care procedures such as skipping the use of masks and other standard procedures are independent risk factors for peritonitis. 9 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 13 , 35 Patient self-care abilities can be obtained through structured training patterns or criteria to enhance knowledge, skills, and attitudes. 54 , 55 Poorly performed self-care procedures such as skipping the use of masks and other standard procedures are independent risk factors for peritonitis. 9 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…All of these conditions indicate that the acceptance of training program patterns or criteria is highly influenced by the capabilities and involvement of individual participants, companions, or family members, as well as the competencies of the trainers themselves. 35 , 44 , 54 , 57 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies associated these outcomes with patient–doctor contact, others did not [ 4 , 10 ]. In studies where positive relationships were reported, patients had an opportunity to be involved in their plan of care and receive education about their treatment [ 11 , 12 , 13 ]. These care conditions contribute to establishing a solid rapport between patients and doctors [ 7 , 8 , 12 , 13 , 14 , 15 ] and are linked to improved quality of care, patient safety, and satisfaction, including reduced medical errors and mortality [ 3 , 4 , 5 , 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%